EXPLORING THE PARADOX OF MSME GROWTH DURING RAMADHAN - Mubaroq, Afiq Chamim; Rafinda, Ascaryan; Setyorini, Christina Tri; Nasihin, Ihsan; Rahmajati, Emir Surya; Alhendi, Osama (EL DINAR: Jurnal Keuangan dan Perbankan Syariah, 2025)
This study aims to examine the dual impact of Ramadan on MSMEs in Indonesia, where increased consumer demand coincides with supply chain disruptions, rising costs, and logistical challenges. The research employs a qualitative descriptive approach with text mining techniques to collect data from various trusted online media sources. The findings indicate that while Ramadan creates significant economic opportunities for MSMEs, challenges remain in meeting market demand. This study highlights the paradoxical nature of this period, underscoring the need for strategic interventions from stakeholders to help MSMEs navigate the complexities of Ramadan. The implications also extend to policymakers, who must consider tailored support to maximize benefits while mitigating the challenges faced by MSMEs during this critical period.